Geochemistry and Sr-Nd isotopic studies of Precambrian gneisses from central Aravalli Craton, NW India: Implications for crustal evolution and reworking. Issue 8 (1st December 2022) - Samiullah Hamidullah, Ismail; Erfan Ali Mondal, Md.; Ahmad, Iftikhar; Rahaman, Waliur; Kumar Dash, Jitendra
Graphical abstract: Highlights: Basement gneisses of Aravalli Craton studied to understand Precambrian crustal evolution. Basement gneisses characterized into sodic and potassic types. Sodic gneisses were derived from an enriched source at ∼3.0 Ga. Potassic gneisses formed during Paleoproterozoic by reworking of pre-existing sodic gneisses. Significant correlations found between sodic gneisses of BGC-I and BGC-II tectonic domains. Abstract: The Aravalli Craton of the Indian shield constitutes heterogeneous basement lithologies (Banded Gneissic Complex; BGC), and among them, the granitoids are the most voluminous lithology. The BGC comprises two lithotectonic units, viz., BGC-I and BGC-II. The BGC-II has been further classified as amphibolite facies Mangalwar and granulite facies Sandmata Complexes. In the present study, the gneisses of the Mangalwar Complex are geochemically categorized into (i) low-and high-pressure sodic gneisses and (ii) potassic gneisses. The sodic gneisses are metaluminous and characterized by high Sr/Y and LaN /YbN ratios; and exhibit subduction-related negative anomalies of Nb and Ti. The εNd (t = 2992 Ma) ranges from +2.3 to +3.1, with an average Nd-depleted mantle model age (TDM ) of 3.06 Ga. The whole-rock Sm-Nd isochron age is ∼3.0 Ga (2992 ± 340 Ma). Genetically, the sodic gneisses originated from the melting of an enriched precursor (oceanic plateau) in an arc environment. These gneisses show strong correlations with the gneisses from BGC-I depicting similar geochemical signatures. In contrast, the potassic gneisses are characterized by slightly higher SiO2 along with high K2 O and high large-ion lithophile elements and negative Eu anomalies along with negative εNd (t = 1.7 Ga) (−13.2 to −3.9), higher initial 87 Sr/ 86 Sr isotopic ratios and average TDM = 2.87 Ga. These geochemical features of the potassic gneisses indicate that they were derived from the reworking of the pre-existing TTG-like (sodic gneisses) crust during the Paleoproterozoic Era.